A bibliometric analysis of the of cybersecurity policy research - Qorahman, Opik; Akbar, Nova Nauval (Jurnal Informatio, 2024)
The cybersecurity policy is a fundamental framework for developing a robust defense strategy for an organization's digital landscape. It involves various critical steps, including classifying information based on sensitivity, implementing strict access control, encrypting data in transit and at rest, continuous security awareness training, an incident response plan for addressing security breaches, deploying network security measures such as firewalls and intrusion detection systems, and physical security protocols to protect data centers and infrastructure. The purpose of this study is to answer the following questions: How are articles on Cybersecurity Policy classified? What are the latest study trends in Cybersecurity Policy analysis? What are the most frequently published research topics? What are the potential areas for future research in Cybersecurity Policy analysis? This research used a quantitative-descriptive technique. This bibliometric analysis explores the extensive and dynamic domain of cybersecurity policy, examining academic outputs from various dimensions. Utilizing standardized methodologies, including Mendeley software, VOSviewer, and PoP, this study navigates the complex terrain of academic literature. The findings reveal major topics such as 'Cybersecurity policy,' 'Network security policy,' and 'Cybersecurity' emerge, illuminating both well-explored areas and less developed fields such as 'National cybersecurity' and 'Cyberspace.' These unexplored aspects present intriguing avenues for future research.